Concept and essence of state policy in the field of education - Maksymenko , Nataliіa; Novitska , Iryna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article defines and summarizes the content of the concept of «politics». It is found that politics is a rather complex and multifaceted phenomenon which covers various aspects of public life. The essence of politics lies not only in the formation and exercise of state power, but also in ensuring stability, justice and development of society as a whole. It serves as a mechanism that regulates the interaction between individuals, social groups and the state, and determines the ways of distributing resources, power and influence on social relations. The scientific views on the interpretation of «public policy» are highlighted. The author offers her own understanding of the concept of «public policy» as a systematic process of decision-making, development of strategies and programs aimed at forming a public demand and determining the regulatory framework for achieving specific public goals, carried out by public authorities and aimed at regulating various spheres of public life.It is established that scholars use various synonymous formulations to denote the concept of «state policy in the field of education», including: «state educational policy», «national educational policy», «state policy in the field of education».By studying the scientific positions and approaches to defining the essence of the concept of «state policy in the field of education», a thorough analysis of this concept is carried out and the author’s vision of the phenomenon under study is formed. The author emphasizes the need to reboot the State policy in the field of education under martial law and the need to implement European principles, approaches and practices in the educational and scientific space.